Women’s Rights and Colonization in The Short Story of The Jakarta Post - Ferdinal Ferdinal (Vivid: Journal of Language and Literature, 2020)
Right after the fall of Suharto’s regime, Indonesia has undergone tremendous changes in almost all aspects of life: political, economic, social, cultural, and possibly ideological lives. The changes bring new breaths to Indonesian future, especially in the area of women’s rights. This article discusses the issue of women’s rights in Indonesia based on a textual analysis. The purpose of this writing is to investigate the representation of women’s rights issues in some stories of The Jakarta Post, one of the most popular media which has also played an important role in popularizing and spreading such issues. Postcolonial criticism is used to see how the stories portray the issues of women’s rights, particularly gender equality and marginality. To study the issues, this analysis looks at two short stories: “Gender Equality” by Iwan Setiawan and “Street Smart Mom” by Eric Musa Piliang.  The two stories represent the fact that Indonesian women fight against colonization for their rights in some different ways, as a smart wife and a poor street mother. The stories signal that Indonesian women struggle to escape from colonization through some actions such as moving forward to the center of power by maintaining superiority against men and living their lives as they wish in spite of being poor.